Studi Penerapan Arsitektur Regionalisme Pada Fasilitas Pertunjukan Kesenian Sandur Di Bojonegoro - Barri, Alfan; Tohar, Ibrahim (Jurnal Etnik: Ekonomi-Teknik, 2024)
This paper discusses the implementation of regionalism architecture principles in the sandur art performance facility in Bojonegoro Regency, East Java. The research aims to apply the principles of regionalism architecture to sandur art performance facilities to accommodate and develop traditional Bojonegoro art. The research method employs a mixed approach with qualitative analysis and observation. Data is obtained through direct observation, literature studies, and analysis of regionalism architecture principles. The analysis of regionalism architecture principles includes responses to local context, the use of local materials, adaptation to climate, and traditional aesthetics. The implementation results in a response to the local context, referring to the sandur art story, which will be used as a zoning boundary on the site. Abundant local materials in Bojonegoro Regency such as red bricks, bamboo, and teak wood, are used. Utilization of sunlight as natural lighting, adequate drainage systems, and utilization of wind as natural ventilation are also applied. Moreover, ornamentation on the building uses teak wood carvings at the entrance and walls, and applies shape transformation from sandur during the kalongking scene, symbolizing the human life cycle. The implementation of regionalism architecture principles in adequate sandur art performance facilities in Bojonegoro is expected to increase public interest, especially among the younger generation, in preserving and learning traditional art of Bojonegoro, become a tourist attraction, and enrich local culture.